Analytical Study Of Last Rotation Biomechanical Variables Before Performing Leaving, Grapping And Landing In Horizontal Bar In Men's Gymnastics - Abbas, Saadullah (Journal of Physical Education, 2017)
Motor analysis plays an integral part in specifying biomechanical errors inperformance specially movements that require speed. Leaving and grabbing using one handis one of the basic requirements of horizontal bar thus the aim of this research is to identifythe most important biomechanical variables in the last rotation before leaving, grabbing andlanding in horizontal bar in men's gymnastics. The researcher videotaped the Chinesegymnast who is one of eight gymnasts in men's singles in Al Doha Championship. Thecamera takes 120 pix/sec. the biomechanical variables were extracted and the data werecollected and treated using proper statistical operations. The researcher concluded that thevariables understudy during landing differs and its values reach the first and second quarters.Finally the researcher recommended paying attention to these biomechanical variablesduring performance on horizontal bar in men's Gymnastics